Exploring the relationship among stress, psychological wellbeing, and performance in healthcare professionals and healthcare students - Berry, Nazm (2023)
Background: The prevalence of high stress in healthcare professionals (HCPs) and healthcare students has gained immense attention over the past decade; and more so since the onset of the COVID-19 pandemic. High levels of stress have been shown to have adverse consequences on the psychological wellbeing, and aspects related to performance, in both HCPs and healthcare students, and particularly in the nursing sector. While prior quantitative research has demonstrated a significant relationship among stress, psychological wellbeing and work performance in HCPs worldwide, there is a need to better understand the factors entailed in this dynamic relationship, and gain more in-depth insight from a qualitative perspective too, particularly in nurses working for the National Health Service (NHS). Likewise, such factors warrant further exploration in nursing students too as they comprise a highly stressed population as compared to students in other fields due to the prevalence of complex and challenging issues that start to arise early in their education and training. Besides exploring the various stressors and factors associated with stress and other aspects of psychological wellbeing and performance, it is also important to look into the various coping strategies and resources that are employed in nursing staff and students within the context of stressful situations, including their uptake and views of available wellbeing courses or other sources of support offered within the healthcare settings.